2021
DOI: 10.1021/acs.jpcc.1c01809
|View full text |Cite
|
Sign up to set email alerts
|

Function and Electronic Structure of the SnO2 Buffer Layer between the α-Fe2O3 Water Oxidation Photoelectrode and the Transparent Conducting Oxide Current Collector

Abstract: The tin oxide buffer layer between the transparent conducting oxide current collector and the hematite photoelectrode causes considerable water oxidation enhancement of that electrode. The water oxidation onset potential is lowered by 180 mV. The lifetime of photogenerated charge carriers is increased by a factor of 10. For the investigation of structure and function of the buffer layer, we designed a wedge-shaped multilayer film assembly. Oxygen 1s X-ray photoemission spectra suggest a decrease of oxygen vaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…They have shown that addition of copper is expected to boost the metallic character of the catalyst that allows for faster charge transfer . In recent years, a number of studies on the growth of thin buffer layers on different substrates have been performed and have led to the enhancement of water oxidation via the improvement of its properties. Song et al have synthesized an electrocatalyst with Ni interfacing between Ni 3 N and nickel foam (Ni 3 N/Ni/NF) for the HER and hydrogen oxidation reaction (HOR) . The catalyst imparted close to zero onset potential in alkaline and neutral electrolytes, demanding an overpotential of only 12–19 mV to afford a current density of −10 mA cm –2 for HER.…”
Section: Introductionmentioning
confidence: 99%
“…They have shown that addition of copper is expected to boost the metallic character of the catalyst that allows for faster charge transfer . In recent years, a number of studies on the growth of thin buffer layers on different substrates have been performed and have led to the enhancement of water oxidation via the improvement of its properties. Song et al have synthesized an electrocatalyst with Ni interfacing between Ni 3 N and nickel foam (Ni 3 N/Ni/NF) for the HER and hydrogen oxidation reaction (HOR) . The catalyst imparted close to zero onset potential in alkaline and neutral electrolytes, demanding an overpotential of only 12–19 mV to afford a current density of −10 mA cm –2 for HER.…”
Section: Introductionmentioning
confidence: 99%
“…[52][53][54][55][56][57][58][59][60][61][62] However, nanostructuring always entails elongation of the electron path to the current collector, which hinders efficient transport of electrons. Here, heterostructuring [63,64] with conductive but still transparent layers can be a direct solution. We adopted our ATO ALD process to form a conductive layer inside a nanotubular array of α-Fe 2 O 3 to see its efficacy for electron transport by comparing the PEC performance with that of the cell without an ATO layer, as schematically shown in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…The porous nature of the films, beneficial for catalysis, can also bring some drawbacks that are associated with shunting recombination in the area where the substrate is in contact with the electrolyte. To avoid this problem, the addition of an isolating underlayer of a few nanometers-such as Ga 2 O 3 [157], TiO 2 [158], SnO 2 [159], or even the deposition of a top polymeric layer [61]-has been successfully explored. Our group's latest work incorporated the underlayer approach to the improved PP methodology [160].…”
Section: Polymeric-precursor Solution-based Methodsmentioning
confidence: 99%